BAURANPEMASARANSUSUFORMULAMORINAGAPADAPT.KALBENUTRITIONALCABANGJAMBI THEMARKETINGMIXEOFMORINIAGAMILKFORMULAATPT.KALBENUTRITIONALATJAMBIBRANCH - Erni Anggreini (DIGEST MARKETING, 2012)
Themarketingprogramforabusinessisnotonlyaimingatsellingtheproductsbutalsotoprovidecustomersatisfaction.ThepurposeofthisresearchistoinvestigatemarketingmixprogramimplementationofPT.KalbeNutrituonalinJambiBranch.Methodusequalitativedescreptivetool.Theresultshowsthatthefirmshasimplementedmarketingmix,buttheimplmentationshouldbeconductedcreatively.Keywords.Product,proce,distribution,andpromotion.